Common clinical presentations in dogs and cats - Englar, Ryane E. (Hoboken, NJ : Wiley-Blackwell, 2019)
'Common Clinical Presentations in Dogs and Cats is a reliable resource and quick reference to essential information for diagnosing canine and feline patients, based on presenting complaints. The text takes a problem-oriented approach to recognizing common clinical conditions, and introduces diagnostic and treatment plans for companion animal practice. Equally useful for veterinary students and practicing clinicians, the book presents 78 chapters grouped by body system, for ease of access. Each chapter focuses on identifying the chief complaint, pinpointing possible diagnoses, and determining the clinical approach to patient care. The book is richly illustrated throughout with clinical photographs and line drawings that demonstrate the concepts presented. Common Clinical Presentations in Dogs and Cats is an essential resource that: * Gives clinicians fast access to essential details for approaching common case presentations in dogs and cats and forming a correct diagnosis * Presents information by clinical signs, organized by body system * Takes a standardized chapter format for ease of use * Includes color photographs and line drawings to illustrate the conditions discussed Written for small animal general practitioners and veterinary students, Common Clinical Presentations in Dogs and Cats is a patient-side reference that can help practitioners gain the knowledge and confidence to correctly diagnose a wide range of clinical presentations'--Provided by publisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Dogs -- Diseases; Cats -- Diseases; Dog Diseases; Cat Diseases; Dog Diseases -- diagnosis; Cat Diseases -- diagnosis; Handbook; Electronic books